Speaking the Unspeakable: Silence Under Surveillance in Two Chinese Science Fiction Stories - Yang, Xin (Surveillance & Society, 2026)
How do people negotiate their agency while they are deeply entangled with the reality filtered or revised by the authorities via pervasive surveillance? How does science fiction, or literature in general, identify the issue and stage the confrontation between the watchers and the watched? This paper discusses the politics of silence under surveillance in two Chinese science fiction (SF) stories, Ma Boyong’s “The City of Silence” (2005) and Zhang Ran’s “Ether” (2012). Placing the texts in the trajectory of Chinese SF’s critical reflection of and intervention into social reality, I argue that the two SF stories speak out the unspeakable, literarily and metaphorically, thematically and aesthetically. The unspeakable means a state of being silent due to the probing eyes and ears of technology. In narrative, the stories delineate how silence is imposed and employed as a rejection to the pervasive eyes and ears. While it is a matter of disempowerment, not letting the surveillant hear also disrupts the power of surveillance. In aesthetics, science fiction is a genre that speaks out within the system, in which non-conformist/different voices are silenced. To speak or not speak, hide or not hide, disguise or not disguise: such dilemmas bring up ethical and moral challenges as surveillance is legitimized and normalized.